5(y+x)-4(y+3x)=

Simple and best practice solution for 5(y+x)-4(y+3x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y+x)-4(y+3x)= equation:


Simplifying
5(y + x) + -4(y + 3x) = 0

Reorder the terms:
5(x + y) + -4(y + 3x) = 0
(x * 5 + y * 5) + -4(y + 3x) = 0
(5x + 5y) + -4(y + 3x) = 0

Reorder the terms:
5x + 5y + -4(3x + y) = 0
5x + 5y + (3x * -4 + y * -4) = 0
5x + 5y + (-12x + -4y) = 0

Reorder the terms:
5x + -12x + 5y + -4y = 0

Combine like terms: 5x + -12x = -7x
-7x + 5y + -4y = 0

Combine like terms: 5y + -4y = 1y
-7x + 1y = 0

Solving
-7x + 1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-7x + 1y + -1y = 0 + -1y

Combine like terms: 1y + -1y = 0
-7x + 0 = 0 + -1y
-7x = 0 + -1y
Remove the zero:
-7x = -1y

Divide each side by '-7'.
x = 0.1428571429y

Simplifying
x = 0.1428571429y

See similar equations:

| 8(2+5r)=-144 | | -25+2=50 | | 5+3(7-x)+6x=-42 | | m^2-34m=0 | | 1/3x3.14x42x42x84 | | 19u-11u-4u=16 | | 1=k/6-3 | | 4/9*m=8/3 | | 8q-1/4q | | k/6-3 | | 18d-17d-d+d=18 | | 3/2*t=90 | | 12h+3h-6h-3h+2h=16 | | .25x-4+.75x=16+.25x-10 | | 27x-14-11x=4(4x-4)+2 | | -18+12g=(12+6g) | | 3/2*t=990 | | 5=6+z | | 15k-15k+k=9 | | 2(x+9)=8(2x-40) | | 6/48=x/8 | | 2y-y-y+y=11 | | 151=-x+7(-6x+3) | | 28=3+8(z-7) | | 3(12)=a(a+5) | | -151=-x+6(-6x+3) | | 2X+3=(X+5)*(X+5) | | 11q-7q=20 | | -20y+1=2-16y+11 | | 10.66+y=28.66 | | 3x-1=(X+5)*(X+5) | | 3x-21=9x+54 |

Equations solver categories